Endoplasmic reticulum stress and oxidative stress are involved in ZnO nanoparticle-induced hepatotoxicity. Issue 1 (2nd April 2015) - Yang, Xia; Shao, Huali; Liu, Weirong; Gu, Weizhong; Shu, Xiaoli; Mo, Yiqun; Chen, Xuejun; Zhang, Qunwei; Jiang, Mizu
Highlights Administration orally with ZnO nanoparticles (Nano-ZnO) caused disruption of ER structure and function in hepatocytes, resulting in ER stress. Nano-ZnO also caused ER stress-associated genes and proteins upregulation and hepatocyte apoptosis. ER stress may be involved in Nano-ZnO-induced liver injury.